Progress and Trends of Multiple Antennas Technology in LTE Network - Qi Bi; Weiliang Xie; Peng Chen (Dianxin kexue)
Multiple antenna technology is considered as one of the few that has the potential to provide relatively large gains in wireless mobile network. The recent progress of using multiple antenna technology in commercial LTE network in China was discussed. By focusing on LTE-FDD network, details of simulation results and measurements from commercial networks were provided to demonstrate the obtainable gains in the real world when compared with theoretical predictions. Based on the current state of art, an outlook at the future trends of the multiple antenna technology with discussions on road maps, challenges and standard progress was given.